Suitability of otolith microchemistry for stock separation of Baltic cod - Heidemann, F.; Marohn, Lasse; Hinrichsen, Hans-Harald; Huwer, B.; Hüssy, K.; Klügel, A.; Böttcher, U.; Hanel, Reinhold (Marine Ecology Progress Series, 2012)
Microchemical otolith analyses have been shown to provide valuable information on the life history, dispersal and stock characteristics of teleost fish. In the present study, the suitability of this technique for identifying the origin and distribution of Atlantic cod Gadus morhua L. from the Baltic Sea was examined using laser ablation-ICPMS. The capacity to distinguish individuals from different Baltic Sea stocks and from the adjacent North Sea stock based on incoporation of stock-specific elemental fingerprints along otolith growth axes was investigated. It was further tested if different origins led to spawning-site specific element concentrations in otolith cores. The results indicate that microchemical analyses of Baltic cod otoliths are applicable for differentiating individuals of different stocks. Analyses of similarities including 12 element/calcium ratios resulted in significant differences between individuals from the eastern and the western Baltic Sea and between North Sea and Baltic Sea samples. Sr/Ca, Ba/Ca, Y/Ca, Mg/Ca, Zr/Ca and Mn/Ca ratios had the strongest discriminatory power. A further separation of individuals caught in 3 different spawning grounds of the eastern Baltic, however, was not possible. Elemental compositions from the core regions of otoliths from young of the year cod caught in eastern and western Baltic Sea spawning grounds showed significant differences in Sr/Ca, Ba/Ca and Mg/Ca concentrations. Analyses of similarities again showed significant differences between these areas for juveniles. This study demonstrates the potential of otolith microchemical analyses to provide important information about the stock structure and connectivity of G. morhua in the Baltic Sea.